The political crisis of 1720: jurisdictional conflicts and political culture of the Ancient Regime in the administration of the Captaincy of Rio Grande in the XVIII century - Lira, Abimael Esdras Carvalho de Moura (Em Perspectiva, 2020)
With this paper will analyze a series of conflicts that occurred in the Captaincy of Rio Grande, across the 1720s, involving the scribe of the Natal’s chamber, Bento Ferreira Mousinho, and the Captain-General that captaincy, José Pereira da Fonseca. Culminating in the José Pereira da Fonseca’s arrest in 1731, aiming from this case study, discuss and characterize the political culture in the present administration of the captaincy of Rio Grande. Therefore, we will analyze some handwritten sources on this conflict, present in the manuscript sources Archive Overseas History (letters, requirements, provisions and appointments) and the terms of the town council of Senado da Câmara de Natal, based on the New Political History discussions.